A case of AL amyloidosis presenting with refractory ventricular fibrillation. (2021) - Angsubhakorn, Natthapon; Agdamag, Arianne; Sumransub, Nuttavut; Velangi, Pratik; Freund, Robert; Martin, Cindy M.; Alexy, Tamas
Abstract: A 66-year-old male with recent diagnosis of heart failure with reduced ejection fraction was referred to our institution for management of cardiogenic/vasodilatory shock. During his evaluation, he suffered a sudden cardiac arrest from refractory ventricular tachycardia/fibrillation (VT/VF) despite normal electrolytes and no evidence of prior ventricular arrhythmias. He was placed on rescue peripheral veno-arterial extracorporeal membrane oxygenation support (VA-ECMO) for 4 days and was decannulated without end-organ damage. Continued workup revealed Mayo stage IV immunoglobulin light chain (AL) amyloidosis. Unfortunately, he developed acute cerebellar hemorrhage several days later. Autopsy findings were consistent with AL amyloidosis, with extensive cardiac fibrosis and amyloid deposition in the myocardium and vasculature. While the most common cause of cardiac death in patients with amyloidosis is severe bradycardia and pulseless electrical activity, sustained ventricular arrhythmias have been reported. The use of implantable cardioverter defibrillators (ICD) is highly debated in this population given the lack of survival benefit. Our patient also developed refractory VT/VF arrest, and ICD shocks would not have rescued him while causing significant distress. Emergent VA-ECMO cannulation allowed us to make a diagnosis, yet this intervention cannot be routinely recommended given the limited survival of patients with AL amyloidosis.